History Teaching and Narrative Tools: Towards Integrating English-Speaking Youth into Quebec’s Social Fabric - Zanazanian, Paul (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2016)
Based on an analysis of five English-speaking students’ written narratives on Quebec’s history, this article proposes a pedagogical tool for better integrating and vitalizing these students’ language community in Quebec. Despite tendencies of reliance and opposition emerging from their historical consciousness, these students do not employ clearly articulated and coherent English-speaking storylines for positioning themselves as a minority group. To this end, I suggest the creation of schematic narrative templates of English-speaking Quebec’s collective historical experiences for offering students workable springboards to develop personal narratives of belonging, while taking Francophone concerns of linguistic and cultural fragility into account.